Negotiating class, ethnicity and modernity: the ‘Malaynisation’ of P. Ramlee and his films - Ahmad, Mahyuddin; Lee, Yuen Beng (Taylor & Francis (Routledge), 2015)
Early Malaysian national cinema disseminates a social reconstruction process aimed at reconstructing Malay supremacy at the centre of a specific geographical, political, economic and cultural space. Aptly termed as ‘Malaynisation’, this process occurred during the Golden Age of Malaysian cinema through the films of P. Ramlee. While existing as a capitalist film culture located within an ethnically diverse society, early Malaysian cinema through Ramlee have produced a significant number of monoethnic representations solely focused on the culture, language and lifestyles of the Malays. As such, the articulation of the politics of inclusion and exclusion in Ramlee’s films articulates a right-wing nationalist sentiment that upholds the sovereignty of the dominant Malays while undermining other ethnic communities. The nature of these representations enunciates the context of an ‘imagined community’ which locates the formation of a particular type of nationalism within a social, political and cultural communicative space. This paper examines the construction of the ‘modern Malay’ identity in Ramlee’s films and the nationalist discourse in Ramlee’s films as an attempt at producing the idea of a nation as a continuous narrative of national progression by presenting the postcolonial Malays as a modern, successful and dominant force